2017
DOI: 10.5897/ajmr2017.8608
|View full text |Cite
|
Sign up to set email alerts
|

Isolation and characterization of extremely halotolerant Bacillus species from Dead Sea black mud and determination of their antimicrobial and hydrolytic activities

Abstract: This is the first study that investigated the isolation of extremely halotolerant Bacillus species from Dead Sea black mud. Nine isolates obtained from black mud were considered to be extremely halotolerant Bacillus based on morphological, physiological, and biochemical properties. Most of their colonies were white to light yellow and circular to irregular. All isolates were Gram-positive rod-shaped endospore-forming bacteria, facultative anaerobes, oxidase negative, catalase positive, mesophilic, extremely ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
7
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 13 publications
(7 citation statements)
references
References 30 publications
0
7
0
Order By: Relevance
“… Product Microorganism isolated from Dead Sea Hydrolytic enzymes Alpha-amylase Bacillus spp. [ 68 ]. Thermostable amylase, also stable at acidic conditions Bacillus strain HUTBS62 [ 69 ] Thermostable amyloglucosidase Halobacterium sodomense [ 70 ] Elastase Bacillus licheniformis 6t2 and 7t1 [ 68 ] Lipase Bacillus spp., Dead Sea mud [ 68 ].…”
Section: Biotechnological Applicationsmentioning
confidence: 99%
See 3 more Smart Citations
“… Product Microorganism isolated from Dead Sea Hydrolytic enzymes Alpha-amylase Bacillus spp. [ 68 ]. Thermostable amylase, also stable at acidic conditions Bacillus strain HUTBS62 [ 69 ] Thermostable amyloglucosidase Halobacterium sodomense [ 70 ] Elastase Bacillus licheniformis 6t2 and 7t1 [ 68 ] Lipase Bacillus spp., Dead Sea mud [ 68 ].…”
Section: Biotechnological Applicationsmentioning
confidence: 99%
“…[ 68 ]. Thermostable amylase, also stable at acidic conditions Bacillus strain HUTBS62 [ 69 ] Thermostable amyloglucosidase Halobacterium sodomense [ 70 ] Elastase Bacillus licheniformis 6t2 and 7t1 [ 68 ] Lipase Bacillus spp., Dead Sea mud [ 68 ]. Cellulase Halomicroarcula pellucida strain GUMF5 [ 71 ] Malate dehydrogenase Halobacterium sp [ 72 ].…”
Section: Biotechnological Applicationsmentioning
confidence: 99%
See 2 more Smart Citations
“…Bacillus persicus 24-DSMisolated from Dead Sea mud provided activity against B. subtilis and E. coli [79]. Another discovery revealed that the Bacillus species DSM2 from the same location has activity against pathogenic fungi, including C. albicans ATCC 10231 and A. brasiliensis ATCC 16404 (Maher 2017) [80].…”
Section: Biopotency Of Halophiles As Antibacterials For Clinical Drug...mentioning
confidence: 99%